ROLE OF ORGANIZATIONAL COMMUNICATION IN CBT PLANNING PROCESS FOR PABUARAN VILLAGE AS RELIGIOUS TOURISM - Patricia Robin; Maria Bianda; Amanda Kristanti (Dinasti Publisher, 2021)
Communication is very important in human life, especially in organizations. Certainly, organizationl behaviour involves communication. Without communication within the organization, organizing effort may not run smoothly. The researcher will raise how organizational communication occurs between the government and the people of Pabauran Village to improve its the tourism. In this research, a qualitative method which involved an interpretation process on the condition of the natural subject is used. The strategy of this case study leads to derivative social units with steps starting from collecting data with active participant observation and interviews, then analyzing the organizational communication relationship within the organization in its management with the Village Officials, data processing, and analysis that produces conclusions. The results obtained were Community -Based Tourism (CBT) which is a village that has a culture of harmony between religious communities is needed through implementation of downward communication within the managing officials.